Benefits of owner mandated CM/GC contract amendment templates. Issue 3 (6th July 2015) - Feuer, Matt; Glick, Scott; Clevenger, Caroline M
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore how implementing a standardized/owner-mandated template for Construction Manager/General Contractor (CM/GC) contract amendments can minimize errors. The focus is on public owners who manage multiple CM/GC projects at any one time. Design/methodology/approach – A case study format was used to compare contract amendments errors using a baseline project, transition project and best practices project. Six metrics were identified, including factual recital errors, summary formatting errors, schedule of values errors, construction services fee errors, allowance schedule errors and data consistency errors. Findings – The baseline and transition projects both had an average of seven errors per amendment, while the best practices project produced zero errors. The amendment template creation process helped design out common errors. The use of the template can be contract-mandated, while transition projects require owner commitment. Research limitations/implications – Future research should focus on completed projects' closeout data that have been consolidated since the transition project was in its final stage and the best practices project was relatively early in the construction process. Practical implications – The findings of this research indicate that by implementing a mature owner-mandated CM/GC contract amendment template, owners can greatly reduce errors that arise during the amendment process. It should be noted, however, that challenges will most likely occur during the implementation phase. Originality/value – No similar studies were found and the results of the research informs Facilities Management departments that they can significantly reduce errors by utilizing a mature, owner-mandated template for CM/GC contract amendments.